IDENTIFIKASI INFEKSI CACING GOLONGAN Soil Transmitted Helminths (STHs) PADA ANAK USIA SEKOLAH DASAR DI DESA TALAWAAN ATAS KECAMATAN WORI - Lalangpuling, Indra Elisabet; Ganing, Nauvila Salsabila; Katiandagho, Dismo; Suwarja, Suwarja (poltekkes kemenkes pontianak, 2024)
Helminthiasis remains a public health problem in Indonesia, particularly among elementary school-aged children. This is due to geographical factors, socioeconomic conditions, and behaviors that neglect hygiene. Infection with Soil-Transmitted Helminths (STHs) can have detrimental effects on children's health and development. This study aimed to determine the prevalence of STH infections among elementary school children in Talawaan Atas Village, Wori District, North Minahasa Regency. This study employed a descriptive method. Samples were examined using both native and Kato-Katz methods. The study sample consisted of 30 elementary school students from GMIM Talawaan Atas who met the inclusion and exclusion criteria. Data was collected through fecal examination and questionnaires. The results showed that of the 30 samples examined using the native method, 3 samples (10%) were found to be infected with STHs, specifically Ascaris lumbricoides. Using the Kato-Katz method, the same 1 sample (3.3%) was found to be infected with Ascaris lumbricoides. The conclusion of this study is that there is a 10% prevalence of STH infections among elementary school children in Talawaan Atas Village, Wori District, North Minahasa Regency.